SEEING THE BELLY DANCE AS A FEMINIST POSSIBILITY: GAZE, GENDER AND PUBLIC SPACE IN ISTANBUL - Egrikavuk, Isil (Cena, 2021)
This paper discusses the ancient form of belly dance as an example to speak more in depth about the public spaces of Istanbul, where the female body is constantly under surveillance by the male gaze. Over thousands of years, the ancient dance form of belly dance has been transformed from a collective women’s ritual to a form of entertainment that serves the male gaze. This paper looks for the possibilities tore-define belly dance as a feminist counter strategy to revive its essence. Framed by the Muted Group Theory, this paper also exemplifies various artworks and strategies produced by female artists and analyze them in the light of this theory. It also searches for redefining the belly dance as part of a feminist identity and asks whether these artistic strategies could be pathways in re-defining belly dance as a feminist practice. Keywords Feminism. Public Space. Belly Dance. Muted Group. Gender.